Технологічне забезпечення ступеня точності зубчастого колеса - Гуліда, Едуард (КІНПАТРІ ЛТД, 2013)
The technological providing of degree of exactness of the treated gear-wheel is considered taking into account technological heredity of exactness of treatment in transition from previous to every next operation of technological process of his making.
Technological providing of degree of exactness gear-wheel